PERAN SIKAP DALAM MEMEDIASI PENGARUH PENGETAHUAN LINGKUNGAN DAN PERSEPSI HARGA TERHADAP NIAT PEMBELIAN HIJAU PRODUK PANGAN ORGANIK - Suratno, S; Rekarti, Endi; rachbini, Didik j. (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
Increasing public awareness of DKI Jakarta to support environmental conservation makes the need for environmentally friendly food products is increasing. However, these needs are not matched by consistency to keep buying these environmentally friendly food products. This study aims to determine the role of attitude in mediating the influence of environmental knowledge and price perceptions on the intention of purchasing green organic food products of residents in DKI Jakarta. The number of population in this research is 6,947,656 million of adult population of DKI Jakarta. The number of samples in this study according to Hair, et. al (2010) which states that the appropriate sample size is between 100 to 200 respondents in order to use interpretation estimation with SEM. The minimum sample size used is 5 observations for each estimated parameter and a maximum of 10 observations from each estimated parameter. In this study the number of research indicators as much as 21 so that the number of samples is 5 times the number of indicators or as much as 5 x (4 + 21) = 125 respondents. The sampling method used is purposive sampling. With the method of analysis using Structural Equation Modeling (SEM). The result of research shows that there are positive significant influence of environmental knowledge variable, price perception, attitude toward the intention of purchasing green organic food product. While the environmental knowledge variable, price perception has no significant effect to purchase intention of green organic food product